Atheism... Plus What? - Carrier, Richard (Essays in the Philosophy of Humanism, 2014)
“Atheism+” or “Atheism Plus” was first promoted by atheist activist Jennifer McCreight, at the suggestion of one of her readers, to describe a movement that had been growing within New Atheism for several years. It is a movement for promoting moral values and the discussion of societal problems among atheists, and for making the atheist community more welcoming of, and responsive to, women and minorities.